KOORDINASI PEMERINTAH DAERAH (PEMDA) KABUPATEN KARIMUN DALAM PENCEGAHAN PERDAGANGAN ORANG TAHUN 2017-2018 - Fikry Herdiansyah; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of conducting this research was to know Kabupaten Karimun local government coordination of prevention of trafficking in persons in 2017-2018. The main problem found in this research is the difficulty of preventing people who want to get a more decent life by working abroad because they have been given the idea of having high wages, then the difficulty of opening jobs with high salaries such as abroad. The theory used in this research was local government, supervision, government coordination, and human trafficking. This research used analytical descriptive method with qualitative research type. The type of data used in this research was primary data and secondary data generated through the results of direct interviews with informants who knew and understood the problems in the field, documentation and observation.Based on the explanation above, it can be concluded that the relationship that affected the implementation Kabupaten Karimun local government coordination of doing prevention of trafficking in persons is carried out on several interrelated factors, such were planning, communication, direction and control.In addition, there were factors hampered coordination of prevention of trafficking in persons, such were low levels of education, easy trust with the invitation of people about the lure of large salaries, Kabupaten Karimun have few job opportunities, and Kabupaten Karimun local government coordination of prevention of trafficking in persons in 2017-2018. Keywords: Coordination, Prevention of Trafficking, Local Government.